Effects of Different Atomization Method on Powder Property, Microstructure and Low Cycle Fatigue Property of FGH97 Alloy. Issue 1 (March 2020) - Tan, J J; Guo, J Z; Long, A P; Li, Q T; Xiao, L
Abstract: Two kinds of Ni-based superalloy powders (P-powder and A-powder) were prepared from masteralloy melted via the process of vacuum induction melting (VIM) by plasma rotating electrode process (PREP) and argon atomization (AA) method, which were used to fabricate two different alloys (P-alloy and A-alloy) using the same hot isostatic pressing process and heat treatment process. The study of microstructure and mechanical properties of FGH97 alloy were conducted to demonstrate the effect of different routes of powders preparation on the microstructure and low-cycle fatigue properties. Results show that the particle size distribution of P-powder is narrower than A-powder, and overall is larger, and the size of the inclusions in the A-powder is much smaller than P-powder. And it has been found that the grain size of A-alloy is finer and γ' phase is more uniform, compared with P-alloy, there is no residual dendrite, grain boundary carbides are intermittent punctate distribution; the strength of A-alloy is slightly higher, and the plasticity is better than P-alloy; at the same time, the crack initiation is formed at the site of slag inclusions, but the size of inclusions of A-alloy significantly smaller; accordingly, the resistance of low-cycle fatigue crack initiation of A-alloy is superior than that of P-alloy due to the fine powder prepared by the process of argon atomization, showing a life time of much more than 150 000 cycles, far better than P-alloy (<70000 cycles); and the fatigue property of A-alloy is very stable.